Fearless beauty 360° : a complete guide to self-acceptance and empowerment - Lee, Kenetia (USA : Changing Lives Press, 2014)
"Have you ever truly, fearlessly, faced down your real reflection in the mirror? In today's world, many women find themselves either frantically chasing, or perhaps completely avoiding their true beauty. Now, one of the country's foremost beauty experts draws from countless intimate interactions with women who have been seated in her own makeup chair to share a rare, uplifting beauty regimen that forges a deeper, more rewarding path to personal beauty."--Jacket flap.
What makes a woman feel beautiful? -- Looking good : what really stands between you and what you desire -- Damaging effects of your internal diva's dialogue -- Revealing reflections : how the past shapes who you see in the mirror every day -- The delusional diva's demise : release the pain that binds you to your fears -- Mindful makeovers : heal the past and change your future -- Beauty's true source : how to trust and listen to your higher self -- Actualizing beauty : reclaiming the fearless child within you -- A declaration of beauty : define and create what matters most to you -- Fearless beauty in action : be it, do it, live it! -- Fearless beauty ritual : putting it all together.
Includes bibliographical references and index.
Keywords: Lee, Kenetia; Self-acceptance.; Beauty, Personal -- Psychological aspects; Self-actualization (Psychology)